The design and application of BIM + refined management and control platform for the Jingxiong railway bridge - Jinghan Zhang; Jiayu Li; Beisheng Liu; Hui Li; Wei Yang (High-Speed Railway, 2023)
The high-speed railway construction involves multiple professional fields, such as railway design, construction, and supervision. This paper architects the ''BIM+ '' project refined management platform, designs the platform's logical architecture, physical architecture, and solves several key technology difficulties. This ''BIM+ '' platform has been applied on the Jingxiong Bridge Project and achieved all-round, whole-process and multi- management of high-speed railway engineering construction. It significantly improves the level of construction management, and plays a role in promoting the development of high-speed railway construction informatization.